2022
DOI: 10.1590/1981-6723.17621
|View full text |Cite
|
Sign up to set email alerts
|

Heme iron fortified flavored milk: quality and sensory analysis

Abstract: The fortification of dairy beverages is a widely developed strategy using non-heme or heme iron. Heme iron has a higher bioavailability. The investigation aimed to elaborate pasteurized milk with fortified chocolate flavor with heme iron that has good sensory acceptability. The preparation of the flavored milk was carried out based on the regulations and heme iron, obtained from a commercial source of whole blood of porcine origin, was added before the pasteurization process to achieve its complete dilution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Iron complexes are known to significantly influence the sensory qualities of milk and dairy products, which warrants further investigation. García et al 82 reported that iron fortification at different concentrations markedly affected the sensory acceptability of milk. Abdulghani et al 83 observed the same outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron complexes are known to significantly influence the sensory qualities of milk and dairy products, which warrants further investigation. García et al 82 reported that iron fortification at different concentrations markedly affected the sensory acceptability of milk. Abdulghani et al 83 observed the same outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…79−81 Iron complexes are known to significantly influence the sensory qualities of milk and dairy products, which warrants further investigation. Garci ́a et al 82 reported that iron fortification at different concentrations markedly affected the sensory acceptability of milk. Abdulghani et al 83 observed the While the iron-fortified cheese exhibited improved functional and structural qualities, it received lower taste ratings, posing a challenge for industrial production.…”
Section: Antioxidant Activity and Sensorymentioning
confidence: 99%